MANAJEMEN PROGRAM LAYANAN BIMBINGAN KONSELING DI MTS NEGERI 2 WAY KANAN - Noprisman, Usman; kurnawati, weni; Pramudya , Esen (UNISAN JURNAL, 2023)
The implementation of guidance and counseling programs plays an important role in supporting the teaching and learning process in schools. The implementation of the guidance and counseling program in the school becomes the guide towards the students’ interest in the school in facing problems in modern times that are full of challenges. However, the success of the implementation of guidance and counseling programs in schools, not only depends on the ability of counselors or counseling teachers, but also depends on good cooperation from all parties in the school itself. It is expected from these parties that support and cooperation will be successful in implementing the guidance and counseling program in the School for the smooth teaching and learning process and the achievement of educational goals. For that to be achieved the effectiveness and efficiency of a planned goal in this case is a guidance and counseling program, quality management is needed as well. MTs N 2 Way Kanan The purpose of this research is to find out counseling guidance service programs that exist in MTs N 2 Way Kanan. in terms of management functions, namely planning, implementation and evaluation. The study was conducted at MTs N 2 Way Kanan. This research uses a qualitative method with a descriptive approach, data collection through interviews, documentation and observation, the data validity test used is triangulation. Data sources in this study are Principals, BK Teachers, Homeroom Teachers, and Students. Based on the results of this study concluded that 1) Planning guidance and counseling programs in MTs N 2 Way Kanan The onion bone is already good, covering 3 stages; a) Preparation of program activities consisting of setting goals, formulating programs such as annual, monthly and daily programs, b) Preparation of personnel, is carried out so that the implementation of the BK program can run well, so that there is no overlapping of responsibilities and tasks. c) Provision of necessary facilities includes; Guidance room and equipment for the room, consisting of: Data storage and whiteboard and bulletin boards. 2) Counseling Guidance in MTs N 2 Way Kanan is not good, there are some guidance and services that have not been maximally implemented, this is caused by 3 things, namely a) Non-linear background of the BK Teacher’s education so that the service performed is less than optimal, b) Lack of socialization of the BK program, and c) Limited time. 3) Evaluation has not been done well, because it has not been able to measure accurately the effectiveness of the BK program implemented, and the absence of a clear evaluation design is a major factor in the difficulty of measuring program success.